Terapi Oksigen Pada Pasien PPOK Dengan Gangguan Pertukaran Gas Di Ruang Intesif Care Unit (ICU) - M Valent Diansyah; Rumentalia Sulistini; Aguscik Aguscik (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2026)
characterized by progressive airflow limitation and impaired gas exchange caused by long-term exposure to harmful particles such as cigarette smoke. This study aimed to describe the implementation of oxygen therapy in patients with COPD and gas exchange disorders in the intensive care unit. Methods: This study used a descriptive case study design. Data were collected through interviews, physical examinations, and monitoring of oxygen saturation and arterial blood gas values. The subjects were two COPD patients who experienced dyspnea and were treated in the ICU. Oxygen therapy was administered using a non-rebreathing mask, combined with the Fowler position, for three consecutive days. Results: The study results showed different responses in the two patients. The first patient experienced an increase in oxygen saturation and improved blood gas analysis values (pH 7.39, pCO₂ 39.6 mmHg, pO₂ 98.5 mmHg), with SpO₂ approaching 98%. In contrast, the second patient showed a decline in oxygenation, characterized by a decrease in SpO₂ to 87% and unstable blood gas analysis values (pH 7.19, pCO₂ 55.9 mmHg, pO₂ 49.8 mmHg). Conclusion: Oxygen therapy combined with postural management can help improve gas exchange impairment in COPD patients; however, the therapeutic response may vary among patients depending on their clinical condition. Therefore, continuous monitoring of patients with gas exchange impairment is necessary, combining independent nursing interventions with collaborative care.